Mejora del proceso de mantenimiento de transformadores mediante el diseño de un modelo de cálculo de la capacidad para el taller eléctrico de Coopelesca R.L. - González-Barrantes, Beatriz Adriana (Instituto Tecnológico de Costa Rica, 2016)
This project was developed in the electric garage of COOPELESCA R. L, in Ciudad Quesada, San Carlos. It consisted in the design of a model to calculate the garage capacity since the maintenance work to the electricity distribution system’s equipment was unknown. The project’s scope involves only the study of transformers because these represented the 75.2% of workflow in the garage. The times of the maintenance processes were calculated in the present situation analysis, resulting in a total of 81 possible combinations for the types of maintenance in transformers. Besides, the productive and improductive activities sampling results in 29% of the workday dedicated to improductive activities. The design of the model separates the individual and the group time for each type of transformers maintenance. The model generates the using of the operating and non-operating capacity and provides a final report. Two alternatives were proposed to improve the operational capacity. One of these consisted on reducing delays during times of maintenance processes through a workplace design and a digital record of test results. The second alternative involved the design of the workplace and process flow redistribution. For the alternatives evaluation, a scenario was tested with the times found in the present situation analysis and it resulted in a total of 88,39 operative hours, applying the changes to the first proposal a 1.67 hours reduction was obtained, and the second proposal showed a 0.55 hours reduction. In conclusion, the first alternative represented the major improvement of operational capacity; however, it requires the major investment, so it is recommended to start with the implementation of the second alternative in the short-term period and in a long-term assess the use of digital record of maintenance results.
Proyecto de Graduación (Licenciatura en Ingeniería en Producción Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Producción Industrial, 2016.
Keywords: Medición del tiempo; Diseño del Puesto de trabajo; Mejora de procesos